Measurement of Medial Tibial Eminence Dimensions for the Clinical Evaluation of ACL-Injured Knees: A Comparison between CT and MRI - Stepanyan, Hayk; Nazaroff, Jaron; Le, Ngoc; Parker, Robert; Tando, Toshimi; Yoshioka, Hiroshi; Wang, Dean (The Journal of Knee Surgery, 2021)
Anterior cruciate ligament (ACL) injuries commonly lead to translational and rotational tibiofemoral instability. The morphology of the medial tibial eminence (MTE) has received increased attention regarding its role in tibiofemoral stability in ACL-injured knees. Therefore, quantification of MTE dimensions on clinical imaging may help clinicians predict knee stability after ACL injury. Although magnetic resonance imaging (MRI) is routinely obtained in patients with ACL injuries, whether the dimensions of the MTE can be accurate quantified on MRI is unknown. The purpose of this study was to assess the degree of correlation between measurements of MTE height and width on computed tomography (CT) versus MRI. An institutional picture archiving and communication system imaging database was used to identify patients aged between 15 and 60 years who received concurrent MRI and CT of the same knee within a 1-year interval. Knees with significant arthrosis, deformity, intraarticular fracture, or hardware-related artifact that obscured visualization of the MTE were excluded. Mean differences and interstudy agreement between CT and MRI MTE measurements were compared using concordance correlation coefficient (rc) and Bland–Altman analysis. A total of 41 knees in 38 patients (mean age, 37 years; 82% male) were analyzed. Interrater reliability for CT and MRI measurements was high (intraclass correlation coefficient = 0.740–0.954). On coronal CT and MRI, mean MTE height measurements were 10.4 ± 1.9 and 10.4 ± 1.8 mm, respectively; mean MTE width measurements were 14.6 ± 3.6 and 14.2 ± 3.0 mm, respectively. On sagittal CT and MRI, mean MTE height measurements were 11.6 ± 1.7 and 11.7 ± 1.7 mm, respectively; mean MTE width measurements were 36.5 ± 4.8 and 36.2 ± 5.0 mm, respectively. Good agreement was observed between CT and MRI measurements of MTE height and width on coronal and sagittal planes (rc = 0.947–0.969). Measurements of MTE height and width were similar on MRI relative to CT on both coronal and sagittal planes. MRI may be suitable for characterizing the dimensions of the MTE when clinically evaluating patients with ACL injuries, potentially allowing for individualized patient care.
Keywords: knee imaging; tibial eminence